Optimizing land use and management at farm level: Implementation of FarmDESIGN recommended optimizations in Lemmo Woreda, Ethiopia - Eshetae, Awoke Meron; Ebrahim, Mohammed; Getachew, Tesfaye; Abera, Wuletawu; Tamene, Lulseged (2024)
Managing mixed farming systems to achieve multiple goals, such as maximizing productivity and minimizing environmental impact, while adhering to farm and policy constraints, is a complex challenge. The intricate interplay between various farm components and the trade-offs among them necessitates a sophisticated approach to decision-making. The FarmDESIGN (FD) model offers a promising solution by capturing these complexities and providing data-driven recommendations. This study applied the FD model to three distinct farm typologies (low, medium, and high resource endowment) in the Lemmo of Central Ethiopia. The model was optimized to maximize operating profit and organic matter balance, while minimizing labour requirements. The optimization results revealed a delicate balance between the objectives, showcasing trade-offs and synergies among them. Cloud of solutions was identified, each with varying levels of performance for each objective. Focus group discussions (FGDs) with farmers highlighted a positive reception to the FD model's recommendations. The proposed interventions included: Improved crop residue management, Organic input application, Intercropping, Forage production and Livestock upgrades. The implementation of FD-recommended interventions has commenced and is progressing steadily. However, seasonal variations and other factors may influence the pace of implementation. Overall, by leveraging the power of the FD model and engaging with farmers, it is possible to develop sustainable and resilient mixed farming systems that can contribute to food security, environmental conservation, and rural livelihood.